Epigenetic modifications of DNA and RNA in Alzheimer’s disease - Martinez-Feduchi, Paula; Jin, Peng; Yao, Bing (Frontiers in Molecular Neuroscience, 2024)
The authors would like to thank the reviewers for their thorough evaluation and constructive feedback. We thank the reviewers for their quality assessment of the review, noting that it "is well written and structured", and their acknowledgement of high interest to a general audience. We have revised the manuscript to provide further clarification on the initial submission based on the comments from the reviewers. We have provided point-by-point responses to fully address the comments by the reviewers, and these responses are provided below. All changes in the manuscript were marked by blue font.Thank you, we have added the information on the samples used in these publications (lines 298-299): "…that has been validated in vitro and in vivo across several human and mouse tissues and cell lines." 7.-line 316: please add "in mice" Thank you, we have clarified the model (line 348-349): "…have been associated with neuroinflammation, axon guidance, and neurogenesis in mice and rats". 8.-line 317-318: "Insulin is essential for glutamatergic signaling, BBB integrity, vasodilation, neuronal318 proliferation, differentiation, cognition, and memory." please add references Thank you for your comment. We wanted to clarify that the reference is listed at the end of the following sentence to avoid repeating the citation (line 353).Please add references. This is a key scientific statement. Thus, my suggestion is that it should be properly and thouroghly supported by references. Otherwise, the role of insulin in the several processes mentioned should be smoothed. Your reply that a reference is included at the end of the paragraph to avoid repeating the citation is unsatisfactory."We thank the reviewer for taking the time to provide such detailed guidance. We have added references to support these claims and provided additional sources (lines